Internalisasi Nilai-nilai Islami untuk Anak Tunagrahita: Program Pembiasaan Religiusitas di SLB Islam Qothrunnada - Vikasari, Diniati Putri; Husna, Difa’ul; Alghozi, Alan Alifudin; Zain, Raihan; Kusuma, Bayu Candra (YASIN, 2023)
The research was conducted with the aim of describing the religiosity habituation program, describing the methods used to internalize the religiosity habituation program for mentally retarded children, and identifying inhibiting and supporting factors in efforts to instill religiosity in mentally retarded children at the Qothrunnada Islamic Special School (SLB). This research uses a qualitative descriptive method by conducting observations, interviews, and also documentation. Development is also carried out in research through literature studies with reference to journals and related sources. The results showed that the Qotrunnada Islamic Special School (SLB) Qothrunnada Islamic SLB had several religious habituation and character support programs. The programs are habituation of disciplined behavior, habituation of carrying out 3S (smile, greeting, greeting), habituation of performing Dhuha prayers in congregation, habituation of Quran literacy, habituation of cleanliness, habituation of congregational midday prayers, MTQ extracurricular program, habituation of neatness, and habituation of respecting the opposite sex.